Data Journalism in Football’s Tactical Analysis on YouTube Channel Ruang Taktik - Abdul Latif Hanafi; Adi Sujana (Jurnal Komunikasi, 2026)
Sports news, particularly soccer, is a common journalistic product in Indonesia. However, few sports media outlets use a data journalism approach to strengthen their soccer narratives. The YouTube channel Ruang Taktik stands out with content that dissects soccer tactics through game strategy analysis combined with data. This article aims to examine the application of data journalism in soccer tactical analysis content on the Ruang Taktik YouTube channel, filling a gap in research on data journalism products in the field of soccer, particularly in Indonesia. The method used in this study is qualitative content analysis. This was conducted by examining eleven soccer match analysis videos from March 2025. The research findings indicate that the Ruang Taktik YouTube channel uses visual spotlights as a data analysis tool to provide a clear visual overview, focuses on ball movement to strengthen content structure, and employs statistical and tactical language as a narrative strategy to help the audience comprehensively understand match analysis. These three elements form a data narrative that integrates match clips as qualitative data with quantitative statistical elements. This study demonstrates that data-driven tactical analysis content on digital platforms can serve as a model for educational and credible sports data journalism in Indonesia.